Dynamics of Suspended Material Carried out From the Flysch Bystrzanka Catchment During Selected Rainfall Events in the Period of 1997-2008 - Kijowska, Małgorzata; Bochenek, Witold (Quaestiones Geographicae, 2011)
Hydrometeorological conditions in Research Station in Szymbark were analysed, and then the influence of these conditions on the water level. The investigations were carried out during the selected high stage in the period 1997-2008. Relations between the precipitation totals, discharge and changes of the amount of material carried away were analysed. Percentage of the suspended matter in complete denudation from the catchment area of the Bystrzanka was also assayed. The results showed that more than 95% of suspended material can be carry out in a single flood. Parameters regarding to the transport of suspended matter in the period 1997-2008 were referenced to the same parameters estimated in the period 1971-1979, and the load of suspended material in the review period was higher by 26%.